P606 Use of TNF-α-antagonists and systemic steroids is associated with attenuated immunogenicity against SARS-CoV-2 in fully vaccinated patients with Inflammatory Bowel Disease. (21st January 2022) - Otten, A T; Bourgonje, A R; Horinga, P P; van der Meulen, H H; van Leer-Buter, C C; Dijkstra, G; Visschedijk, M C
Abstract: Background: Patients with Inflammatory Bowel Disease (IBD) frequently use immunomodulating treatment, which may render them at increased risk of attenuated immunogenicity after vaccination. Immunosuppressive drugs, such as TNF-α-antagonists, have shown an attenuating effect on serological response after SARS-CoV-2 infection. Here we assessed the effects of different types of immunosuppressive medications on the serological response after vaccination against SARS-CoV-2 in patients with IBD. Methods: This was a prospective observational cohort study in patients with IBD of whom IgG antibody titers were measured after 2–10 weeks after full vaccination against SARS-CoV-2. Patient demographics, clinical characteristics as well as a previous history of SARS-Cov-2 infection, type of vaccine (mRNA or vector), and medication use were recorded at time of sampling. The primary study outcome was the anti-SARS-CoV-2 spike (S) antibody concentrations, measured using chemiluminescence microparticle immunoassay (CMIA) after full vaccination. Results: 312 IBD patients were included (172 Crohn's disease [CD] and 140 ulcerative colitis [UC]). Seroconversion (defined as titer of >50 AU/ml) was achieved in 98, 3% of patients. Antibody concentrations were significantly lower in patients treated with TNF-α-antagonists vs. non-users of TNF-α-antagonists (geometric mean [95% confidence interval]: 2204 [1655–2935] vs. 5002 [4089–6116] AU/ml, P<0.001). In multivariable models, use of TNF-α-antagonists (percentage decrease -88%, P <0.001), age (>50 years) (-54%, P <0.01) and CD (vs. UC) (-39%, P <0.05) were independently associated with anti-SARS-CoV-2 antibody titers. In patients who received mRNA vaccines, users of systemic steroids demonstrated significantly lower antibody titers compared to patients who were steroid-free (geometric mean [95% CI]: 3410 [2233;5210] vs. 5553 [4686–6580], P <0.05). Conclusion: TNF-α-antagonist use is strongly associated with an attenuated serological response after vaccination, independent of the type of vaccination (mRNA/vector), the time interval between vaccination and sampling, prior SARS-CoV-2 infection and patient age. Patients treated with systemic steroids who received mRNA vaccines demonstrated lower anti-SARS-CoV-2 antibody titers compared with patients who were steroid-free at time of serology.